Saliva and Blood Asprosin Hormone Concentration Associated with Obesity - Ugur, Kader; Aydin, Suleyman (Hindawi Ltd, 2019)
Background. The aim was to investigate the amounts of saliva and serum asprosin in order to determine whether it is related to obesity and whether salivary glands synthesize asprosin or not. Methods. A total of 116 underweight, normal weight, overweight, and obese (class I, class II, and class III) volunteers participated in the study. Saliva and blood samples were collected simultaneously from the participants. The amounts of asprosin in saliva, salivary gland tissue supernatants, and bloods were determined by ELISA, whereas asprosin synthesis sites of salivary gland tissues were determined immunohistochemically. Results. The amount of asprosin from the lowest to the highest was in the order as follows: underweight, normal weight (control), overweight, and obese classes I and III. The lowest level of asprosin was detected in underweight individuals. It was also found that the interlobular striated ducts and the interlobular ducts of the submandibular and parotid salivary glands produce asprosin. According to these data, the asprosin level is related with obesity as the amount increases in accordance with increasing body mass index (BMI). On the other hand, there is also a relationship between the underweight and asprosin because the amount decreases with BMI decrease. Conclusions. Asprosin, a new adipokine, may be a novel indicator of adipose tissue mass. Therefore, we anticipate that antiasprosin preparations may be an alternative in the treatment of obesity in the future.
Keywords: Insulin